Role of configurational entropy in body-centred cubic or face-centred cubic phase formation in high entropy alloys. (November 2016) - Anand, G.; Goodall, R.; Freeman, Colin L.
Abstract: This study examines the comparative phase stability of transition and late transition element based high entropy alloys in body-centred cubic (BCC) or face-centred cubic (FCC) forms using a combined classical molecular dynamics and statistical mechanics based approach. Multi-configurational sampling was carried out using a hybrid genetic algorithm-molecular dynamics (GA-MD) based method. The calculations demonstrate that comparative BCC or FCC phase stability is influenced by configurational entropy. The present study also provides a theoretical explanation of the recently reported occurrence of BCC phase in CoCrFeNi HEA, where the high temperature structure may be retained. Graphical abstract: